Inventories and the Propagation of Sectoral Shocks - Cooper, Russell; Haltiwanger, John (American Economic Review, 1990)
This paper contrasts the dynamic properties of an imperfectly competitive economy with a representative agent, real business cycle model. For both economies, inventories are the important dynamic linkage. The predictions of these models with regards to the comovement of employment across sectors may differ. Empirical evidence on the comovement of employment over the business cycle is consistent with the model of imperfect competition with inventory holdings.